Sidelobe level reduction using Teflon for a microwave and millimetre‐wave antipodal Vivaldi antenna. Issue 6 (19th February 2020) - Moosazadeh, Mahdi
Abstract : A new technique for lowering the sidelobe level (SLL) of the microwave and millimetre‐wave antipodal Vivaldi antenna (AVA) has been presented in this study. The technique is based on introducing tapered‐shape Teflon surrounding AVA to couple energy propagated from the antenna and produce stronger radiation in the end‐fire direction and as a result, it offers wideband low SLL. Some features of the presented antenna with the utilised new technique are summarised as follows: high gain in wide bandwidth corrected tilt of beam on E ‐plane in wide bandwidth and low cross‐polarisation level. The presented antenna is fabricated and the magnitude of the reflection coefficient of the fabricated antenna is tested, which is from 3.2–40 GHz with S 11  < −10 dB. It exhibits an average of SLL < −10 dB in E ‐plane and SLL < −18 dB in H ‐plane at a wideband of 3.2–40 GHz. Moreover, the lowest E ‐plane's SLL of −20 dB is achieved over the frequency band of 7–7.5 GHz. The proposed antenna has a small size of 43 (width) × 108 (length) mm 2 . The proposed antenna with the mentioned features becomes an attractive candidate for imaging applications.